Evaluating Surgical Delay Using Infrared Thermography in an Island Pedicled Perforator Flap Rat Model - Li, Xiucun; Chen, Miao; Maharjan, Suraj; Cui, Jianli; Lu, Laijin; Gong, Xu (Journal of Reconstructive Microsurgery, 2017)
Background The aim of this study was to examine the usefulness of infrared (IR) thermography in visualizing the dilation of the choke vessels in a delayed pedicled perforator flap rat model.Methods A three-territory island flap was designed and harvested on one side of the rat dorsum. The flap was divided into five regions. In the normal group (n = 8), IR thermal imaging was correlated with the postmortem arteriography for the location of angiosomes, linking patterns, perforator diameter, and temperature on each region. The delay group (n = 35) was divided into seven groups according to various delay periods. At different time intervals, the delay group was compared with the normal group according to link pattern and temperature on each region.Results IR thermal imaging showed that a white hotspot existed on the surface of each angiosome; the true anastomotic vessels manifested a continuous white band linking the white hotspots on angiosomes, whereas the choke vessels presented a red zone in between adjacent hotspots. After delay, the dilation of the choke vessels manifested itself as the replacement of the red zone between adjacent hotspots by the white band on IR thermography. In addition, the delayed flap presented a phenomenon of rise and fall in temperature over time.Conclusion IR thermography can accurately visualize the process of the dilation of choke vessels after a surgical delay. The chronological change in the IR thermal imaging combined with the temperature change in the delayed flap might be useful to determine the optimal delay period.
Keywords: delay phenomenon; infrared thermography; pedicled perforator flap